Study Of The Behavior Of Anchor Connections In Concrete Based On Finite Element Analysis - Mildariezka Salsabila Ramadhan; Fikri Alami; Mohd. Isneini; Vera Agustriana Noorhidana (JACEE (Journal of Advanced Civil and Environmental Engineering), 2023)
The anchorage system is one of the techniques used to connect a new structure to the existing structure. The purpose of this study was to determine the behavior between the anchorage connection model in the existing column structure and the new beam using an adhesive anchoring system, and the monolithic column-beam structure model using a program based on the finite element method, Abaqus CAE. The analysis was executed on two models, the monolithic construction model and the anchor joint connection structure model. The same load was applied for both models at the ends of the beams. In the monolithic construction model, the interaction relationship between the column and beam is using a tie constraint, while the structure of the anchor joint connection was using surface-to-surface contact. The epoxy model in anchor joint structure were using a cohesive behavior-contact relationship. As the results of the analysis, it can be concluded that the monolithic construction has stiffer joints compared to the structures with anchor joint connections, it can be seen from the displacement value of monolithic construction is 4.263 mm meanwhile structure with anchor connection is 5.38 mm. The crack pattern in the monolithic construction is in the column face on the area around the beam connection, while in the anchor connection, the crack pattern forms a cone in the area around the column anchor.